Question
Solve for x . \[ 2(-x-3)+4 x-4=4 \]
Ask by Blake Mitchell. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( x = 7 \)
Solution
To solve the equation:
\[
2(-x - 3) + 4x - 4 = 4
\]
Let's follow the step-by-step process:
### Step 1: Distribute the 2
Apply the distributive property to the term \(2(-x - 3)\):
\[
2(-x) + 2(-3) + 4x - 4 = 4
\]
\[
-2x - 6 + 4x - 4 = 4
\]
### Step 2: Combine Like Terms
Combine the \(x\)-terms and the constant terms:
\[
(-2x + 4x) + (-6 - 4) = 4
\]
\[
2x - 10 = 4
\]
### Step 3: Isolate the Variable Term
Add 10 to both sides to move the constant to the right side:
\[
2x - 10 + 10 = 4 + 10
\]
\[
2x = 14
\]
### Step 4: Solve for \(x\)
Divide both sides by 2 to isolate \(x\):
\[
\frac{2x}{2} = \frac{14}{2}
\]
\[
x = 7
\]
### **Solution**
\[
x = 7
\]
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
To solve for \( x \) in the equation \[ 2(-x-3)+4x-4=4, \] let's start by simplifying step-by-step. First, distribute the \( 2 \): \[ 2(-x) + 2(-3) + 4x - 4 = 4, \] which simplifies to: \[ -2x - 6 + 4x - 4 = 4. \] Now, combine like terms on the left side: \[ (-2x + 4x) + (-6 - 4) = 4, \] giving you: \[ 2x - 10 = 4. \] Next, add \( 10 \) to both sides: \[ 2x = 4 + 10, \] which simplifies to: \[ 2x = 14. \] Now, divide both sides by \( 2 \): \[ x = \frac{14}{2}, \] resulting in: \[ x = 7. \] So the solution is \( x = 7. \)